Free‐standing Reduced Graphene Oxide/MoO3‐x Composite Film with High Performance for Flexible Supercapacitors. Issue 31 (19th August 2019) - Yu, Ms. Le; Zhao, Shi‐Xi; Wang, Yi‐Feng; Wu, Qi‐long; Zheng, Ms. Xiao‐Xiao; Wei, Guodan; Nan, Ce‐Wen
Abstract: For the fabrication of flexible supercapacitors, the biggest challenge is still the preparation of flexible electrodes with both high gravimetric and areal specific capacitances. Herein, we have successfully designed a novel rGO (reduced graphene oxide)/MoO3‐x composite film electrodes for high‐performance flexible supercapacitor. The as‐prepared electrodes exhibit a galvanostatic capacitance of 1374 F⋅g −1 and an area specific capacitance as high as 21300 mF⋅cm −2 at 0.1 A⋅g −1, which have been significantly larger compared with most recent reports. Meanwhile, the rGO/MoO3‐x composite electrodes have remarkable flexibility and solid mechanical strength. This composite film could be easily folded into various shapes, and then could recover its original appearance without any crease. Excellent cycle stability has also been validated with nearly 100% capacitance retention even after 30, 000 cycles. The electrochemical performance of rGO/MoO3‐x composite films remain surprisingly stable even after continuous U‐shape bending up to 10, 000 times. Moreover, flexible all‐solid‐state symmetric supercapacitors were successfully fabricated with PVA (polyvinyl alcohol)‐H2 SO4 gel electrolyte. Our strategy provides a convenient and versatile method for designing new flexible electrode for energy storage devices and is promising for portable and wearable electronics. Abstract : Free‐standing oxygen vacancies‐contained MoO3‐ x /rGO composite film prepared with vacuum filtration achieved excellent flexibility and electrochemical performance for flexible supercapacitors.